Bottom‐up manipulations alter the community structures of galling insects and gall morphs on Neoboutonia macrocalyx trees in a moist tropical rainforest. (7th April 2014) - Malinga, Geoffrey M.; Valtonen, Anu; Nyeko, Philip; Roininen, Heikki
Abstract The effects of bottom‐up forces on the community structure of tropical insect gallers and within species variation in gall morphotype assemblages are not well understood. We tested the roles of increased nutritional quality and density of host plants with respect to structuring the galling insect communities and gall morphotype assemblages on Neoboutonia macrocalyx trees in Uganda. Plant nutritional quality and resource concentration were manipulated with four levels of fertilization and the group size of trees, respectively. After applying these treatments in May 2011, gallers established naturally on experimental replicates. Five months later, we sampled gallers and recorded their numbers and the different morphotypes. We analyzed the effects of treatments on the structures of galler communities and gall morphotype assemblages. We recorded 5237 individuals, representing four galler species. One species, Cecidomyiid leaf galler, was represented by three morphologically distinct galls. Fertilization, host tree density and their interactions significantly changed the structures of galler species communities and gall morphotype assemblages. The results of the present study demonstrate the important role of bottom‐up factors in structuring galler communities and the gall morphotype assemblages. These changes are likely caused by differential responses of different galler species and gall morphs to plant quality or quantity changes.